On the origin of grain size effects in Ba(Ti0.96Sn0.04)O3 perovskite ceramics. Issue 6 (June 2019) - Tan, Yongqiang; Viola, Giuseppe; Koval, Vladimir; Yu, Chuying; Mahajan, Amit; Zhang, Jialiang; Zhang, Haibin; Zhou, Xiaosong; Tarakina, Nadezda V.; Yan, Haixue
Abstract: Over the last 50 years, the study of grain size effects in ferroelectric ceramics has attracted great research interest. Although different theoretical models have been proposed to account for the variation in structure and properties of ferroelectrics with respect to the size of structural grains, the underlying mechanisms are still under debate. Here, we report the results of a study on the influence of grain size on the structural and physical properties of Ba(Ti0.96 Sn0.04 )O3 (BTS), a ferroelectric compound that represents a model perovskite system, where the effects of point defects, stoichiometry imbalance and phase transitions are minimized by chemical substitution. It was found that different microscopic mechanisms are responsible for the different grain size dependences observed in BTS. High permittivity is achieved in fine-grained BTS ceramics due to high domain wall density and polar nanoregions; high d33 is obtained in coarse-grained ceramics due to a high degree of domain alignment during poling; large electric field-induced strain in intermediate-grained ceramics is an outcome of a favorable interplay between constraints from grain boundaries and reversible reorientation of non-180° domains and polar nanoregions. These paradigms can be regarded as general guidelines for the optimization of specific properties of ferroelectric ceramics through grain size control.